Determinants of Organization of Dialogical Self - Personalistic Perspective - Gasiul, Henryk (Studia Psychologica: Theoria et praxis, 2008)
The presented article comprises an analysis of conditions which determine the organization of dialogical self. It is hypothesized that a dialogue between I-positions is determined by the way in which these I-positions can gratify I-motives. The author presumes that I-motives are a manifestation of personal attributes which are typical for the nature of human beings. I-positions which are able to gratify personal attributes would also be experienced as gratifying selfenhancement (S) and union with others (O) motives. Personal attributes are treated as a more fundamental source of I-motives than motives O and S. In this light, the author contends, that the S and O motives should be regarded as indicators of the realization of I-motives. The way of gratification of I-motives becomes a crucial reason for considering the ways of dialogical self organization. At the same time, it seems that only these I-positions, which are, sensu largo, ”permeated” with other person’s presence (only a person allows to realize subject’s attributes such as identity or dignity) would have special meaning; only in this perspective the elements of culture, the past and future figures become meaningful for the subject. It is an interpretation in the spirit of personalistic thinking, which maintains, that all processes can be understood only if they are rooted in personhood and related to person. Consequences of I-motives frustration lead to some form of emotional commitment. A subject is forced by necessity to cope with emotional states and these states restrict possibilities to discover new I-positions. That is why the dialogical self may be in a phase of crisis and in a state of rigidity.